HIPCAR - electronic evidence : model policy guidelines & legislative texts (ITU Place des NationsCH, 2013)
Aims to regulate legal evidence in both civil and criminal proceedings.
HIPCAR's objective is to assist CARIFORUM Countries in the Caribbean to harmonise their information and communication technology (ICT) policies, legislation and regulatory procedures.\n HIPCAR's objective is to assist CARIFORUM Countries in the Caribbean to harmonise their information and communication technology (ICT) policies, legislation and regulatory procedures.\n